Combined continuum mechanics and molecular dynamics approach for uniaxial deformation of a thermoplastic polymer - Bauer, Christof; Pfaller, Sebastian (Proceedings in Applied Mathematics and Mechanics, 2021)
A hybrid molecular dynamics (MD)‐continuum mechanics (CM) method for calculating a molecular system of an amorphous polymer under uniaxial tensile load was developed. In this contribution, the operating principle of this method is introduced and applied to a sample system. Furthermore, the practicability of the hybrid MD‐CM approach is examined.<br